An Ethnography of the Goodman Building The Longest Rent Strike - Caldararo, Niccolo; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Palgrave Macmillan, 2019)
Through in-depth analysis and narrative investigation of an actual building occupation, Niccolo Caldararo seeks to not only offer an historical account of the Goodman Building in San Francisco, but also focus on the active resistance tactics of its residents from the 1960s to the 1980s. Taking as its focal point the building itself, the volume weaves in and out of every life involved and the struggles that surround it-San Francisco's urban renewal, ethnic clearing, gentrification, and municipal governance at a time of booming urban growth. Caldararo, a tenant at the center of its strikes and activities, provides a unique perspective that counteracts current trends in ethnographies of urban movements by grounding its analysis in physical and tangible space.
Part I: The National Context for the Goodman Buildilng -- Chapter 1: The Housing Crisis in America and the Policies That Created and Promote It -- Part II: Setting the Scene of the Goodman Building -- Chapter 2: Preface to the Goodman Building Ethnography -- Chapter 3: The Background and Setting -- Chapter 4. Redevelopment in the Western Addition -- Part III: The Goodman Building in Transition: From Single Room Occupancy for Temporary Workers to Artist Hotel to Community Action -- Chapter 5: Resistance, WAPAC: J-Town Collective, Nihonmachi Little Friends-The Goodman Group; and Coalitions with Architectural Preservationists -- Chapter 6: A Broader Field: BART, TOOR and the I-Hotel -- Chapter 7: Beat Rebels with a Cause, Hippies and Community -- Chapter 8: The Monday Night Meeting: "These Are Artists, You'll Never Get Them Organized!" San Fransisco Art Commissioner -- Chapter 9: Living in an Art Community -- Part IV: Communities of Change and Occupation -- Chapter 10: Learning From Others and Spreading the Word -- Chapter 11: Democracy At Home -- Chapter 12: Media Darlings, Art Scene and Money: Saving the Goodman Building -- Chapter 13: Repression, Reaction and Retrenchment -- Chapter 14: The Strike Ends, Losing the Goodman Building -- Part V: A New Start in a Changing City -- Chapter 15: Assessment, and a New Goodman Building in the Era of Go-Go Capitalism -- Chapter 16: Conversations at G2: The New Goodman Building Interviews with Tenants at the 18th Street Complex.
Keywords: Ethnology; Culture -- Study and teaching; Sociology, Urban; Social structure; Equality; Ethnography; Sociocultural Anthropology; Cultural Studies; Urban Sociology; Social Structure